Fictionalizing heterodoxy Various uses of knowledge in the Spanish world from the Archpriest of Hita to Mateo Alemán - Gernert, Folke (De Gruyter, 2019)
The information overload produced by the printing press and the new forms of the structuring of knowledge are echoed in fictional works. The essays assembled in this book study the textualization of problematic forms of knowledge in medieval and early modern Spanish literature. Literary Works like the Libro buen amor, La Lozana Andaluza, or the Guzmán de Alfarache are read against the backdrop of scientific developments of their times.